Ultrathin graphene oxide membrane with constructed tent-shaped structures for efficient and tunable molecular sieving. Issue 8 (14th July 2020) - Yang, Kaijie; Pan, Tingting; Hong, Seunghyun; Zhang, Kun; Zhu, Xiaoying; Chen, Baoliang
Abstract : Tent-shaped ultrathin GO membrane for tunable molecular sieving. Abstract : Graphene oxide membranes (GOMs) continue to attract intense interest because of their promising two-dimensional channels. However, finely adjusting a GOM's interplanar spacing for tunable molecular separation is still challenging in aqueous solution. Herein, we report tent-shaped interplanar channels that can be constructed by loading SiO2 nanospheres (diameter ≈ 30 nm) into ultrathin GOMs (thickness ≈ 20 nm). The tent-shaped structure takes advantage of the augmented space to accelerate the flux while utilizing the preserved circumjacent nano-channel as a molecular sieve. Particularly, by adjusting the density of intercalated SiO2 nanospheres, the concomitant interlayer channel can be finely tuned with molecular-level accuracy. Precise selectivity makes the SiO2 loaded GOM (SGM) capable of separating molecules with sub-nanometer differences. At the same time, under the premise of the same rejection, tunable channels endow SGMs with 1.3–63 times higher permeability than that of a pristine ultrathin GOM. This tent-shaped structure supplies a new avenue for GOM structural regulation, and the impressive performance demonstrates its great potential in the fields of water purification and membrane filtration.